Project Shikamana: Community Empowerment-Based Combination HIV Prevention Significantly Impacts HIV Incidence and Care Continuum Outcomes Among Female Sex Workers in Iringa, Tanzania. (1st October 2019) - Kerrigan, Deanna; Mbwambo, Jessie; Likindikoki, Samuel; Davis, Wendy; Mantsios, Andrea; Beckham, S.Wilson; Leddy, Anna; Shembilu, Catherine; Mwampashi, Ard; Aboud, Said; Galai, Noya
Abstract : Objective: To determine the impact of a community empowerment model of combination HIV prevention (Project Shikamana) among female sex workers (FSW) in Iringa, Tanzania. Methods: We conducted a 2-community randomized trial. Intervention elements included the following: (1) Community‐led drop‐in center and mobilization activities; (2) venue-based peer education, condom distribution, and HIV testing; (3) peer service navigation; (4) provider sensitivity trainings; and (5) SMS reminders. We used time-location sampling to enroll 496 FSW and conducted a survey and blood draws to screen for HIV and assess viral load at 0 and 18 months. We conducted an intent-to-treat analysis using logistic and Poisson regression and inverse probability weighting for primary outcomes. Results: The analysis included 171 HIV-positive and 216 HIV-negative FSW who completed baseline and 18-month study visits. Participants in the intervention were significantly less likely to become infected with HIV at 18-month follow-up (RR 0.38; P = 0.047), with an HIV incidence of 5.0% in the intervention vs. 10.4% control. Decreases in inconsistent condom use over time were significantly greater in the intervention (72.0%–43.6%) vs. control (68.8%–54.0%; RR 0.81, P = 0.042). At follow-up, we observed significant differences in behavioral HIV care continuum outcomes, and positive, but nonsignificant, increases in viral suppression (40.0%–50.6%) in the intervention vs. control (35.9%–47.4%). There was a strong association of between higher intervention exposure and HIV outcomes including viral suppression. Conclusions: Project Shikamana is the first trial of community empowerment-based combination prevention among FSW in Africa to show a significant reduction in HIV incidence warranting its broader implementation and evaluation.